Impactos do crédito produtivo nas noções locais de sustentabilidade em agroecossistemas familiares no território sudeste do Pará. - Silva, Luis Mauro Santos (2008)
In a region of the amazon agrar frontier, this study tried to evaluate the actual state of the familiar agro-ecosystems impacted by the productive credit access considerating the local notion of sustainability and its multidimensional character.Involving a territorium with seven towns from the southeast of Pará, 16 agro-ecosystems served as a comparison of the instrument application MESMIS (Mark for evaluation of the Systems for Management of the natural resources incorporating Indicators of Sustainability) .The evaluation way counted with the participation of local actors resulting on the definition of 10 composed indicators incorporated on the 3 dimensions: environmental, social and technic- economical. The aplication of semistructurated interviews, questionaries, camp diary and direct observations garanted the instrument application. The construction of the local concept was the first step to comprehend the reality and with it we assegured the most relevant aspects, externalizated by the local actors. The agro-ecosystems evaluated on the assettlement La Estância demonstrated a lot of fragility on their sustainability; all of them get grades below 6,0/10,0. The low perspectives to exercises the citizenship was one of the most critical points observed. The credit access has increased the familiar patrimony and reduced the necessary of selling the familiar labour force, even if it is until now- very low flexible and has difficulties for potentialized the local experiences. About the promissives evaluated agro-ecosystems, we constated either much fragility on the evaluated dimensions geting all with grades above the 6,5/10,0. At least, the sustainability concept learned locally seems to be coherent with the studied context and, therefore much operative. In a context marked by the absence of infra-structure on the assettlements and by diverse environmental limitations, these families stay distant from the meaning of sustainability concerning to the multidimensional aspects considering the improvement of some social and economical indicators from the available productive credits. We also concluded that this fails are noticed and revealed by local notions of sustainability showing the fragility of the credit policies for attend the equilibrium among the dimensions socio, economical, environmental and the development strategies. Brazilian Amazon, familiar agro-ecossystems, indicators, sustainability.